2017
DOI: 10.1515/hukin-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Mechanical and Neuromuscular Profile of Knee Extensor and Flexor Muscles in Professional Soccer Players at the Start of the Pre-Season

Abstract: The aim of the study was to determine the mechanical and neuromuscular profile of knee extensor and flexor muscles in professional soccer players at the start of the pre-season, and to calculate percentages for symmetry, as well as examine differences according to the player’s positional role. The vastus medialis (VM), vastus lateralis (VL), rectus femoris (RF) and biceps femoris (BF) of 16 professional soccer players were evaluated by means of tensiomyography (TMG) on the first day of the pre-season. A paired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 34 publications
5
24
0
1
Order By: Relevance
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 88%
“…15.40% vs. 8.13% lower values, for Dom and NonDom leg, respectively), which may suggest a higher level of fatigue of the participants during the testing in the aforementioned study. In a study conducted by García-García et al (2017) the mean values (dominant and non-dominant leg), of the Tc variable, were 34.5±6.6 ms, and for variable Dm they were 7.0±1.7 mm, which is higher by Tc and lower by Dm in relation to our study. One of the possible reasons for the mentioned findings and differences in relation to the results of this study can be explained by an interpretation of testing the sample of football players of a different level of competition, application of tests in a different training period, as well as the size and structure of the sample.…”
Section: Discussionsupporting
confidence: 53%
“…Vastus lateralis and vastus medialis did, however, display asymmetry with regard to Tc [ 74 ]. A study with a similar population showed less than 10% bilateral asymmetry in vastus medialis and up to about 20% asymmetry in the vastus lateralis, rectus femoris and biceps femoris [ 108 ]. In another study, volleyball players have also shown high levels of displacement symmetry in lower limb muscles, regardless of sex, which is in contrast to the untrained general population [ 50 ].…”
Section: Applications Of Tensiomyographymentioning
confidence: 99%
“…More and more authors7–9 explicitly state the condition that the evaluator should be an expert, which requires that he has made a good number of measurements and its intra-evaluator reliability is very high.…”
Section: Measurement Protocols and Reliability In Athletesmentioning
confidence: 99%